Mathematical model of the system performance mode for simultaneous separate well operation - Kamil R. Urazakov; Alexander S. Totanov; Leila A. Mutalova (Известия Томского политехнического университета: Инжиниринг георесурсов)
Relevance. The trend of oil production technology development is related to many relevant topics. One of such actual directions is the technology of simultaneous separate well operation, in particular, including two electric centrifugal pumps and double-sided submersible electric motor. The presence of two formations at the bottomhole implies the selection of the optimal layout, technological parameters of pumps pumping oil. Considering production from two independent formations in the well according to the mentioned technology, there is a high need in selection of correct parameters of installations at the design stage. In the absence of correct selection of technological parameters of units at the design stage, further operation of a well with two independent formations can be economically inexpedient, and in some cases unrealizable, which is due to a number of reasons. First, if the necessary underbalance is not provided for each particular formation, counterflow of fluid may occur and one of the pumps will not participate in the production process. Secondly, when operating an arrangement, which capacity significantly exceeds the capacity (fluid flow from the reservoir) of the well, there is a possibility of pumping failure and, as a consequence, there is a risk of potential failure. In this regard, an extremely urgent task at the moment is to ensure correct selection of technological parameters of electric centrifugal pump units used in simultaneous separate operation of wells with two independent formations. Aim. Development of a mathematical model that allows selecting the optimal technological parameters of the arrangement consisting of two electric centrifugal pumps and a double-sided submersible motor, used for simultaneous separate operation of wells with two independent formations. Methods. Numerical simulation methods for analyzing the operation mode of electric centrifugal pumps in conditions of oil production from two independent reservoirs. Results and conclusions. It was obtained that the developed mathematical model of the system operation mode for simultaneous separate operation of wells allows to estimate the potential of each individual selected pump during oil production (in time dynamics) by analyzing the depression on each individual reservoir, as well as modeling the process taking into account the potential backflow of liquid and supply failure.